Diabetes Burnout Syndrom With Self Care Agency Diabetes Mellitus Type 2 Patient - Nian Afrian Nuari (State Islamic University of Sunan Ampel, 2018)
Management of Diabetes Mellitus requires commitment and not infrequently makes the patient feel saturated and discouraged. This psychological disorder can result in the management of diet and its treatment. The purpose of this study was to investigate the relationship between Diabetes Burnout Syndrome and Self Care Agency Type 2 Diabetes Mellitus Patients. The study was a cross-sectional study that used Diabetes mellitus type 2 patients using a purposive sampling technique. This study used an instrument in the form of a Diabetes Burnout Syndrom questionnaire measured by an SMBM questionnaire. The Self Care Agency variable was measured using the SCDA (Summary of Self Care Diabetes Activities) questionnaire. Based on the results of this study indicated that most of the respondents have aged 51 to 60 years, male sex, educational background of primary school and have a history of Diabetes Mellitus disease for 1 to 5 years. Based on the research obtained almost all respondents have a low category of Diabetes Burnout Syndrome and have a Self Care Agency enough category. Spearman rho test results obtained relationship between Diabetes Burnout Syndrome with Self Care Agency (p = 0,000, cc = -0,875). It can be concluded that the lower the rate of Diabetes Burnout Syndrome the better the level of Self Care Agency Diabetes Mellitus Patients. Diabetic patients should be able to manage and minimize burnout syndrome that appears to improve independence in treatment and control of blood sugar.